Penerapan Modul Inventor dengan Pendekatan CTL untuk Meningkatkan Kompetensi Siswa pada Mata Diklat CAD - Yatin Ngadiyono; Muhammad Syari'ati Ramadhani (Jurnal Dinamika Vokasional Teknik Mesin, 2016)
The purpose of this study was to determine an applicable framework of CTL learning approaches and improving the competence of students using module as media. This research is a class action research comprising of three cycles. Subjects of this study were students of class XI machining TP 1 at SMK Muhammadiyah 1 Bantul, with 26 students as respondents. The result of this study is a learning framework for CAD with CTL approach. The sequence of this framework are: directing the use of the module and the materials selection, the formation of discussion groups based on students' computer skills, providing motivation and samples of CAD drawings used in the industry, providing drawing jobs that challenge students' knowledge, doing the drawing exercise within the group using the module as a knowledge source, groups discussion to find solutions to the problems, debriefing and reflection, and finally implementing an authentic assessment. Students' competence has increased from the average value of 62.16 and 0% passed the test in the first cycle, to 82.69 and 84.62% passed in the second cycle, and to 80.68 with 100% passed in the last cycle.--------------------------------------------------------------------------------------Tujuan dari penelitian ini adalah untuk mengetahui kerangka pendekatan pembelajaran CTL yang dapat diterapkan dan peningkatan kompetensi siswa dengan media modul. Penelitian ini merupakan penelitian tindakan kelas yang terdiri dari tiga siklus. Subjek dari penelitian ini adalah siswa pemesinan kelas XI TP 1 SMK Muhammadiyah 1 Bantul dengan jumlah responden sebanyak 26 siswa. Hasil penelitian menghasilkan kerangka pembelajaran CAD dengan pendekatan CTL dengan urutan pertama pengarahan penggunaan modul dan penentuan materi, pembentukan kelompok diskusi sesuai dengan keahlian siswa, memberikan motivasi dan contoh pekerjaan CAD di industri, pemberian soal yang menantang pengetahuan siswa, mengerjakan latihan bersama kelompok dengan sumber pengetahuan dari modul, diskusi kelompok untuk menemukan solusi masalah, tanya jawab dan refleksi, dan terakhir melaksanakan penilaian autentik. Kompetensi siswa mengalami peningkatan rata-rata nilai dari siklus pertama 62.16 kelulusan 0% ke siklus dua menjadi 82.69 kelulusan 84.62% kemudian siklus terakhir menjadi 80.68 kelulusan 100%.